2019
DOI: 10.3389/fphys.2019.01317
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Small Vessel Disease (CSVD) – Lessons From the Animal Models

Abstract: Cerebral small vessel disease (CSVD) refers to a spectrum of clinical and imaging findings resulting from pathological processes of various etiologies affecting cerebral arterioles, perforating arteries, capillaries, and venules. Unlike large vessels, it is a challenge to visualize small vessels in vivo, hence the difficulty to directly monitor the natural progression of the disease. CSVD might progress for many years during the early stage of the disease as it remains asymptomatic. Prevalent among elderly ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 284 publications
(375 reference statements)
0
41
0
5
Order By: Relevance
“…There are several etiopathogenic classifications of CSVD. However, the most prevalent forms of CSVD are amyloidal CSVD (sporadic and hereditary cerebral amyloid angiopathy [CAA]) and non-amyloidal CSVD (arteriolosclerosis, agerelated, vascular risk-factor-related SVD, i.e., microatheroma, lipohyalinosis, fibrinoid necrosis, and segmental arterial disorganization) [42,52,53]. Other less common forms of CSVD include inherited or genetic CSVD that is recognizably different from CAA (i.e., Fabry's disease and cerebral autosomal dominant arteriopathy with subcortical ischemic strokes and leukoencephalopathy [CADASIL]), inflammatory and immunologically mediated CSVD (i.e., rheumatoid vasculitis, lupus erythematosus, and CNS vasculitis secondary to infection), venous collagenosis, and other CSVD (i.e., non-amyloid microvessel degeneration in AD and postradiation angiopathy) [42,52,53].…”
Section: Characteristic and Classificationmentioning
confidence: 99%
See 3 more Smart Citations
“…There are several etiopathogenic classifications of CSVD. However, the most prevalent forms of CSVD are amyloidal CSVD (sporadic and hereditary cerebral amyloid angiopathy [CAA]) and non-amyloidal CSVD (arteriolosclerosis, agerelated, vascular risk-factor-related SVD, i.e., microatheroma, lipohyalinosis, fibrinoid necrosis, and segmental arterial disorganization) [42,52,53]. Other less common forms of CSVD include inherited or genetic CSVD that is recognizably different from CAA (i.e., Fabry's disease and cerebral autosomal dominant arteriopathy with subcortical ischemic strokes and leukoencephalopathy [CADASIL]), inflammatory and immunologically mediated CSVD (i.e., rheumatoid vasculitis, lupus erythematosus, and CNS vasculitis secondary to infection), venous collagenosis, and other CSVD (i.e., non-amyloid microvessel degeneration in AD and postradiation angiopathy) [42,52,53].…”
Section: Characteristic and Classificationmentioning
confidence: 99%
“…Despite the growing insights from histopathological, epidemiological, and physiological studies in the past two decades, the underlying pathomechanism of CSVD remains contentious [46,53]. In general, it is recognized that advanced age and the presence of chronic hypertension may reduce the ability to self-regulate cBF in response to various systemic blood pressure levels and increased arterial stiffness, hence the increased speed and flow pulsatility in cerebral arterioles [16].…”
Section: Pathomechanismmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, this emerged evidence did not yield a shred of conclusive pathophysiological evidence as to how it pertains to pulsatile tinnitus. It has been shown that increased arterial stiffness may lead to microvascular damage in the brain and this can manifest itself with a multitude of clinical symptoms and signs including tinnitus [19] . This had yielded to another entity related to carotid system arterial stiffness implicated in the development and severity of "idiopathic subjective tinnitus" [8] .…”
Section: What Is the Prevalence Characteristics And Pathophysiology Omentioning
confidence: 99%